Health Education: Adult Learning in Weight Management Using Weight Tracking Application - Che Pa, Noraini; Md Yasin, Sharifah; Din, Muhammad Nizzan Qussyairi; Jusoh, Yusmadi Yah (Journal of ICT in Education, 2019)
The health management is importance to gurantee a human to achievement for a healthy and ability to do their daily task. In view of the health risks of obesity and its prevalance, it is important to provide health education to adults. Weight management knowledge is necessary for any adults in order to control of being overweight or obesity. Obesity increases the risks of developing  many types of diseases such as hypertensions, diabetes, heart diseases, gallstones, gout and several types of cancer. The problems faced by some adults is they loved to eat a lot and at the same time they are lacking in doing any exercises. The objectives of this paper are mainly to helps Malaysian citizen to monitor and manage their weight properly through Weight Tracking Application (WTA). This application helps user to check their Body Mass Index (BMI), the ideal calories needed for a daily and the ideal body weight. WTA also provide some exercise recommendations and health tips which helps the user to calculate total calories taken per day and to keep track of their weight changes. WTA is a mobile-based application for iOS and Android that used Hypertext Markup Language (HTML5) and Typescript languages. WTA’s users are adults and middle age groups.